Credibility of foreign credibility of foreign discriminatory models in relation to the assessment of the financial condition of Polish enterprises: Case study of E. Altman's Method - Rafał Pitera (e-Finanse: Financial Internet Quarterly, 2019)
The article is an attempt to assess whether foreign discriminatory models can be used in conditions of the Polish economy. To date, there is no one voice on this issue. There are views that this approach is wrong. It results from different factors affecting a given economy, or another character of the economy itself. Another issue is also differences in financial reporting of individual countries, which is translated into financial data. In turn, a different view is presented by the trend that foreign models can be used in the conditions of the Polish economy, while the differences that appear do not significantly affect the quality and reliability of the received diagnosis. Accordingly, the article attempts to verify both above positions. For the purposes of the study, the article presents the results of research on a sample of 25 bankrupt companies from the years 2012 to 2017, which declared liquidation bankruptcy, and their 25 healthy counterparts. The diagnosis of their financial situation was made using E. Altman's model of 1983.
Keywords: M40; G17; G32; G33; 330; E. Altman's Method; methods of the early warning; bankruptcy of enterprises; financial standing of companies; financial analysis